The Expatriate Experience in Dubai: Goal Fulfillment as a Measure of Success - Andrade, Maureen Snow; Miller, Ronald Mellado (Journal of Organizational Psychology, 2018)
Individuals considering expatriate opportunities must examine a number of variables before deciding to relocate. The inability to adjust to the new environment contributes to expatriate failure and comes at significant cost to employer and employee. Variables contributing to success include selection, training, personality, cultural distance, and family adjustment. This study examined factors that influenced goal fulfillment for expatriates in Dubai. Self-preparation, social interaction, relationships, diversity, personality traits, and the desire to learn enhanced adjustment and goal achievement. Selection for expatriate assignments should focus on determining a match between the assignment and employee goals as well as identifying appropriate personality traits.